2020
DOI: 10.1002/mdc3.12965
|View full text |Cite
|
Sign up to set email alerts
|

Management of Advanced Therapies in Parkinson's Disease Patients in Times of Humanitarian Crisis: The COVID‐19 Experience

Abstract: Background Although the COVID‐19 pandemic is affecting a relatively small proportion of the global population, its effects have already reached everyone. The pandemic has the potential to differentially disadvantage chronically ill patients, including those with Parkinson's disease (PD). The first health care reaction has been to limit access to clinics and neurology wards to preserve fragile patients with PD from being infected. In some regions, the shortage of medical staff has also forced movement disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(151 citation statements)
references
References 66 publications
(116 reference statements)
2
138
0
11
Order By: Relevance
“…A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…To answer emerging questions on this topic Fasano et al, conducted a single-centre case-controlled survey describing clinical features/predictors of COVID-19 infection and outcome in a relatively unselected and homogeneous large cohort of PD patients from one of the largest tertiary centers of Milan, Italy [14]. They identified 105 PD patients, 32 confirmed and 73 probable cases of COVID-19.…”
Section: Vulnerability To the Infectionmentioning
confidence: 99%
“…No podemos olvidar que pacientes que manipulan sus sistemas de neuroestimulación y pueden accidentalmente apagarlo e incluso modificar los programas, aunque tienen menor riesgo, también pueden convertirse en una urgencia y es importante que tengan acceso a formas de comunicación ya sea por telemedicina o en el servicio asistencial para dar solución a los problemas de forma oportuna, lo más importante es prevenir el paso de una urgencia a una emergencia, teniendo en cuenta que para la urgencia tenemos 24 horas para atender, mientras que para la emergencia la acción debe ser inmediata (26,27).…”
Section: Manejo De La Medicaciónunclassified
“…En caso extremo de no contar con la medicación en el hospital, debe asegurarse dosis equivalentes de levodopa oral o por sonda nasogástrica con el fin de minimizar las complicaciones. Se debe considerar dejar las bombas desbloqueadas (excepto si existe riesgo de desregulación dopaminérgica) y garantizar un contacto estrecho con el paciente y el cuidador, con el fin de asistir por teleconsulta en los problemas que se presenten, y de esta forma evitar las visitas al hospital (8,27). La figura 1 ejemplifica el esquema de manejo de la enfermedad de Parkinson durante la pandemia, según el grado de complejidad de las terapias avanzadas.…”
Section: Manejo De Sistemas De Perfusión (Apomorfina)unclassified